The effect of Phet Simulation media for physics teacher candidate understanding on photoelectric effect concept - Supurwoko Supurwoko; Cari Cari; Sarwanto Sarwanto; Sukarmin Sukarmin; Suparmi Suparmi (International Journal of Science and Applied Science: Conference Series, 2017)
Indonesian new Curriculum for senior high school students required student-centered learning. One of the curriculum implementation constraint was the difficulty of providing learning media. PhET simulations media is one of the options that can help implementation of new curriculum on learning. However, the use of this media in Indonesia still needs to be studied comprehensively. The learning was conducted on students of physics education Study Program in sebelas maret university in 2013. The sample consisted of 62 students that was taking quantum physics course. The method that was used in the research was descriptive qualitative.  The method that was used in learning was demonstration’s method that used PhET media and accompanied by a question and answer and groups discussion. The data was collected using multiple choice test and interview through email. We found that any students still did not understand about photoelectric effect concept. They were confused when asked about the thick material and cross section of the targets as related with the regardless of electrons in the photoelectric effect event. Other than that, the concept of the waves as a particle and its relation with the kinetic energy of the electrons was not understood by most students.